Congres GKF en opening tentoonstelling "Tijdsbeeld van vandaag ...". Met rede van Tomás Maldonado - Maldonado, Tomás. (1965)
Congres GKF en opening tentoonstelling "Tijdsbeeld van vandaag ...". Met rede van Tomás Maldonado.